Effect of desensitizing treatment for pediatric patients diagnosed with Molar Incisor Hypomineralization (MIH) - Demostene-Raymundo, Adriana Vittorina; De Lima-Martinez, Paola Alexandra; Acosta-de Camargo, Maria Gabriela (Revista Facultad de Odontología Universidad de Antioquia, 2024)
Introduction: Molar Incisor Hypomineralization is a qualitative enamel defect that affects the tooth enamel. This condition is accompanied by Dental Hypersensitivity (DH), given by the high porosity of the affected enamel, generating pain during tooth brushing, when eating cold or hot foods, and during dental consultations. The aim of this research was to evaluate the effect of a desensitizing treatment for pediatric patients diagnosed with MIH. Methods: an observation guide was used, applied to pediatric patients between 6 and 12 years of age, with a sample of 30 affected teeth. The treatment consisted of the application of fluoride varnish and the use of an 8% arginine paste for 30 days, evaluating DH before and after, with the Schiff and Tactile measurement scale. Results: there was found that before the treatment the patients were at level 2 on the tactile scale and level 2-3 on the Schiff scale and after treatment, they were at level 1-0 on both scales. Conclusion: there was a reduction in sensitivity, demonstrating that the treatment may be effective.